Sexual health in relation to religious beliefs: perceptions of young women living in Khayelitsha - Perera, Shehani (Department of Public Health and Family Medicine, 2020)
South Africa continues to have the highest HIV-prevalence in the world, in addition to other sexual health-related issues. A vast majority of its population is also religiously affiliated with Christianity. This study sought to understand how young women living in Khayelitsha experience the relationship between sexual health and religion within the context of uncertainty and socio-economic deprivation. How their sexual health-decision making unfolds given the tensions that arise between religious expectations and socio-economic realities and how they perceive the partnership between religious organisations and public health facilities offering sexual health services was also explored. Data collection consisted of ethnographic field notes, 11 semistructured interviews and 3 focus group discussions with 6 people in each group. Data were then analysed using a thematic analysis approach. The findings reveal that young women experience the tension between religious expectations and their socio-economic realities through the “moral dichotomisation of right and wrong” and that this, in addition to the ‘dynamics of hypervulnerability’ consisting of gender inequalities and economic vulnerability, leads to a sense of lacking control over sexual health decision-making. The call for church involvement in sexual health-related matters reveals a deeper desire for various forms of support as they transition to adulthood in the context of uncertainty and socio-economic marginalisation. The article argues that young people navigating uncertainty and dealing with the complexities of transitioning to adulthood may perceive religion and the church to play the role of a custodian in sexual health issues, however, expectations of the church are difficult to live up to and sit in tension with socio- economic realities. Thus, a division of duties between religious organisations and public health facilities should be established to strengthen sexual health promotion and prevention efforts.